Cognitive Disposition to Wine Consumption: How the Brain Is Wired to Select the Perfect Bottle With a Novel Musical Twist - Soós, Gabriella; Csernák, József; Lakatos, László; Zsófi, Zsolt; Palotás, András (Frontiers in Neuroscience, 2019)
Taste is not a veridical perception: it is modifiable by cognitive and affective processes, as well as by expectations. Even though molecular composition determines the savor, various other factors such as external characteristics and basic assumptions have a sway over perceived pleasantness of food and drink. The rituals associated with wine tastings especially underscore the importance of these subjective ramifications. While auditory stimuli are known to influence drinking experience, the impact of melody on the product itself and on corollary consumer preference is unknown. As routine judgments are also influenced by informational cues, here we evaluated whether description of a unique technological innovation (ie. serenaded grapes and barrels) as cogent suggestion of quality improves willingness to buy. This project unveils that the belief about music-fed wines, which might be construed as a motivational bias, can alter purchasing decisions, however further neuro-marketing studies are warranted with this respect.